Find Remainder of x^2-3x+3 by x+4 using Remainder Theorem
The Remainder Theorem is an approach to Euclidean polynomial division. According to this theorem, dividing a polynomial P(x) by a factor (x - a), which is not an element of the polynomial, yields a smaller polynomial and a remainder. Here you can check the answer for Find Remainder of x^2-3x+3 by x+4 using Remainder Theorem.
Ex: x^2+2x+1,x+1 (or) x^2-1,x-1 (or) x^3-1,x+1
How to Find Remainder of x^2-3x+3 by x+4 using Remainder Theorem?
Let p(x) = x^2-3x+3
The zero of x+4 is = -4.
So after P(x) is divided by x+4 we get the remainder i.e. P(-4).
Now, p(-4) = x^2-3x+3 .
= (3)+(x^2)+(-3.x)
By putting x = (-4) we can rewrite it as
= (3)+((-4)^2)+(-3.(-4))
= (3)+(16)+(12)
= 31
∴The remainder of given polynomial is 31.
FAQs on Remainder Theorem of x^2-3x+3 by x+4
1. What is the remainder of x^2-3x+3 by x+4?
The Remainder of x^2-3x+3 divided by x+4 is 31.
2. How to Find Remainder of x^2-3x+3 by x+4 using Remainder Theorem?
Consider x+4 = 0 so that x = -4.
Substitute x = -4 in expression x^2-3x+3 to get the remiander
Thus, x^2-3x+3 divided by x+4 remainder is 31.
3. Where can I obtain detailed solution steps for Remainder Theorem of x^2-3x+3?
The detailed steps for the Remainder Theorem of x^2-3x+3 are compiled exclusively on our output page.